Introduction to PSpice : a supplement to electric circuits, 4th edition - Nilsson, James William. (Addison-Wesley Pub. Co., 1993)
PSpice in general; Data statements for DC analysis; Control statements for DC analysis; Output statements for DC analysis; Operational amplifiers; Inductors and capacitors; Time-dependent circuit response; Switches; Step response; Varying component values; Sinusoidal steady-state analysis..